How do you solve for X in the equation (2x-3)(x-5)(4x+7)=0?

2 answers

since it's already factored, you can equate each factor to zero and solve for x.
2x - 3 = 0
2x = 3
x = 3/2

x - 5 = 0
x = 5

4x + 7 = 0
4x = -7
x = -7/4

note that there are three values of x.

hope this helps~ :)
solve for x.
(2x-3)=0
(x-5)=0
(4x+7)=0
Similar Questions
  1. Solving Multi-Step Equation Quiz1.Solve the Equation x5=−2 A. -35 B. -10 C.3 2. Solve the equation. x5+1=−7 A. -13 B. -40 C.
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. You need to solve this equation for x: ax−7=26Which would be the best first step you could make to solve the equation? (1
    1. answers icon 5 answers
  3. You need to solve this equation for x: ax−7=26Which would be the best first step you could make to solve the equation? (1
    1. answers icon 22 answers
more similar questions